Comparison between calcium hydroxide mixtures and mineral trioxide aggregate in primary teeth pulpotomy: a randomized controlled trial - Lidiane Lucas Costa e Silva; Leopoldo Cosme-Silva; Vivien Thiemy Sakai; Camila Soares Lopes; Ana Paula Pereira da Silveira; Rafael Tobias Moretti Neto; João Eduardo Gomes-Filho; Thais Marchini Oliveira; Ana Beatriz da Silveira Moretti (University of São Paulo, 2019)
Abstract Objectives: To evaluate the effect of calcium hydroxide (CH) associated with two different vehicles as a capping material for pulp tissue in primary molars, compared with mineral trioxide aggregate (MTA). Methodology: Forty-five primary mandibular molars with dental caries were treated by conventional pulpotomy using one of the following materials: MTA only (MTA group), CH with saline (CH+saline group) and CH with polyethylene glycol (CH+PEG group) (15 teeth/group). Clinical and periapical radiographic examinations of the pulpotomized teeth were performed 3, 6, and 12 months after treatment. Data were tested by chi-squared analysis and a multiple comparison post-test. Results: The MTA group showed both clinical and radiographic treatment success in 14/14 teeth (100%), at all follow-up appointments. By clinical evaluation, no teeth in the CH+saline and CH+PEG groups had signs of mobility, fistula, swelling or inflammation of the surrounding gingival tissue. However, in the CH+saline group, radiographic analysis detected internal resorption in up to 9/15 teeth (67%), and inter-radicular bone resorption and furcation radiolucency in up to 5/15 teeth (36%), from 3 to 12 months of follow-up. In the CH+PEG group, 2/11 teeth (18%) had internal resorption and 1/11 teeth (9%) presented bone resorption and furcation radiolucency at all follow-up appointments. Conclusion: CH with PEG performed better than CH with saline as capping material for pulpotomy of primary teeth. However, both combinations yielded clinical and radiographic results inferior to those of MTA alone.